EVALUASI KINERJA DISEMINASI TEKNOLOGI INTEGRASI TERNAK KAMBING DAN KOPI DI BONGANCINA, BALI - WAYAN SUDANA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
According to AIAT vision and mission, AIAT should be able to develop localspecific alternative package of agriculture technology. This study has been conducted toevaluate the performance of dissemination which has been done by AIAT, especially for theintegration technology livestock (goat) with coffee crop. This evaluation were conducted byinterviewing stakeholder and beneficiaries start from provincial level, district, sub districtlevel, and the end at farmer group. Result of evaluation showed performance of disseminationactivities has been done properly by AIAT, especially at provincial and district level. But atfarmer group especially at target group or target area outside of farmer cooperator not yet wasdone maximally. Dissemination should be emphasized for the target group or target areasimmediately after package of technology described, through some ways of disseminationmethods. Based on SWOT analysis, there are strong opportunity to develop farmer coffeeplantation, because productivity and efficiency of farmer coffee are still low.